Manual versus Automatic Classification of Laryngeal Lesions based on Vascular Patterns in CE+NBI Images - Esmaeili, Nazila; Illanes, Alfredo; Boese, Axel; Davaris, Nikolaos; Arens, Christoph; Navab, Nassir; Friebe, Michael (Current Directions in Biomedical Engineering, 2020)
Longitudinal and perpendicular changes in the blood vessels of the vocal fold have been related to the advancement from benign to malignant laryngeal cancer stages. The combination of Contact Endoscopy (CE) and Narrow Band Imaging (NBI) provides intraoperative realtime visualization of vascular pattern in Larynx. The evaluation of these vascular patterns in CE+NBI images is a subjective process leading to differentiation difficulty and subjectivity between benign and malignant lesions. The main objective of this work is to compare multi-observer classification versus automatic classification of laryngeal lesions. Six clinicians visually classified CE+NBI images into benign and malignant lesions. For the automatic classification of CE+NBI images, we used an algorithm based on characterizing the level of the vessel's disorder. The results of the manual classification showed that there is no objective interpretation, leading to difficulties to visually distinguish between benign and malignant lesions. The results of the automatic classification of CE+NBI images on the other hand showed the capability of the algorithm to solve these issues. Based on the observed results we believe that, the automatic approach could be a valuable tool to assist clinicians to classifying laryngeal lesions.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Classification; Contact Endoscopy; Larynx